Donald J. Trump’s Speech on the Orlando Shooting: Critical Discourse Analysis - Joni Susanto; Rio Satria; Chindy Hanggara Rosa (Дискурс профессиональной коммуникации, 2022)
Maintaining communication may sometimes be ignored by the speaker. One may have a style of offensive and controversial statements while others speak based on the rules of communication without violating the theory of Grice’s conversational maxims. An example of the former is Trump’s speech about the Orlando Mass Shooting on March 16, 2016. Very often Donald J. Trump’s speeches seem to be offensive and controversial. However, some audiences find them effectively acceptable. To explore Trump’s big phenomenon speech, the authors carry out thorough research by applying the Critical Discourse Analysis which focuses on the text dimension. The results of this research are analyzed by using the qualitative approach. The application of the text dimension theory makes it possible to conclude that in the analysed speech Donald Trump successfully delivered his conservative beliefs and values to the audience by utilizing fear and making use of the media and the tragedy which took place in Orlando in March 2016. His victory in the 2016 presidential elections also points to the effectiveness of the speech. This research contributes to the understanding of critical discourse analysis and the way it functions in the study of various social issues.